2007
DOI: 10.1016/j.antiviral.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A model of human cytomegalovirus infection in severe combined immunodeficient mice

Abstract: Animal models for the evaluation of therapies against human cytomegalovirus (HCMV) are limited due to the species-specific replication of CMV. Models utilizing human fetal tissues implanted into SCID mice have been used but tend to be labor intensive and require human tissues. We therefore developed a model using HCMV-infected human foreskin fibroblasts (HFF) seeded onto a biodegradable gelatin matrix (Gelfoam). Infected HFFs are then implanted subcutaneously into SCID mice. We next evaluated two antivirals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Consequently, we assessed the antiviral efficacy of AIC246 in an engineered mouse xenograft model (14). The Gelfoam xenograft model employed has two major advantages over other animal models: first, the appropriate human virus can be used for in vivo evaluation; second, antiviral compounds that show activity only against human cytomegalovirus can be tested (11). Using this animal model, AIC246 shows excellent antiviral efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we assessed the antiviral efficacy of AIC246 in an engineered mouse xenograft model (14). The Gelfoam xenograft model employed has two major advantages over other animal models: first, the appropriate human virus can be used for in vivo evaluation; second, antiviral compounds that show activity only against human cytomegalovirus can be tested (11). Using this animal model, AIC246 shows excellent antiviral efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of mycophenolate mofetil on the development of Tregs is controversial. 16,17,31 Treg numbers are increased after treatment with a combination of mycophenolate mofetil and vitamin D3. 17 However, other experimental studies have not demonstrated relevant negative effects of mycophenolate mofetil on the development and function of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, other experimental studies have not demonstrated relevant negative effects of mycophenolate mofetil on the development and function of Tregs. 31 Furthermore, an experimental mouse study showed that mycophenolate mofetil at therapeutic doses may exert an inhibitory effect on Treg proliferation and function. 16 In the current study, analysis of splenic tissue did not reveal significant differences in Treg counts between the different experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hu-SCID mouse model is difficult to work with and there is potential for variation between labs. A recent innovation of this approach is the use of an artificial surgical gel foam matrix containing HCMV infected human fibroblast cells, which is surgically embedded in the SCID mouse [135]. Potentially, this approach could standardize the model and allow the testing of different human cell lineages and HCMV antiviral therapies.…”
Section: CMV Antivirals and Animal Modelsmentioning
confidence: 99%